Turning challenges into opportunities: Lessons from Ethiopia's COVID-19 response for strengthening health systems and health security. - Muluneh Yigzaw Mossie; Jenny Shannon; Amare Bayeh Desta; Etsub Brhanesilassie; Adugna Dufera; Saira Nawaz (PLOS Global Public Health)
Emerging in late 2019, the COVID-19 outbreak rapidly evolved into an unprecedented global public health crisis. While exposing critical health system weaknesses, the pandemic also spurred innovation and investment, including rapid vaccine development. This paper examines Ethiopia's multi-tiered health system response, exploring the strategies, enabling conditions, barriers, and lessons learned. We conducted a mixed-methods, cross-sectional study across all tiers of Ethiopia's health system from August to December 2023. Data came from three concurrent components: a quantitative survey of implementers (n = 952), key-informant interviews (n = 80), and administrative data. An additional 233 health workers were surveyed to assess intervention integration. Study tools were informed by the Consolidated Framework for Implementation Research and WHO pillars. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent framework analysis, followed by synthesis and triangulation. Results show Ethiopia rapidly expanded laboratory capacity, increasing RT-PCR sites from one (February 2020) to 72 (June 2020), and developed genomic sequencing. Critical care capacity grew, supported by the acquisition of over 764 oxygen concentrators, 320 mechanical ventilators, and remote workforce training. Rapid vaccine deployment and cold chain expansion facilitated over 68 million people receiving at least one dose. The country gained valuable experience in community engagement and deployed over 3,000 rapid response teams. While initial political will and engagement were strong, it waned over time. Consequently, despite efforts to integrate and institutionalize, some key interventions-including surveillance, laboratory testing, and case management-declined as the pandemic's urgent phase passed and political engagement diminished. In conclusion, the Ethiopian health system gained experiences and tools in critical care, laboratory testing, rapid vaccine deployment, and community engagement. If institutionalized and sustained, these capacities can significantly strengthen Ethiopia's health system and enhance its resilience. To fully integrate and institutionalize these platforms for future emergencies, robust monitoring is essential.